First identification and genotyping of Enterocytozoon bieneusi and Encephalitozoon spp. in pet rabbits in China - Lei Deng; Yijun Chai; Leiqiong Xiang; Wuyou Wang; Ziyao Zhou; Haifeng Liu; Zhijun Zhong; Hualin Fu; Guangneng Peng (BMC Veterinary Research, 2020)
Abstract Background Microsporidia are common opportunistic parasites in humans and animals, including rabbits. However, only limited epidemiology data concern about the prevalence and molecular characterization of Enterocytozoon bieneusi and Encephalitozoon spp. in rabbits. This study is the first detection and genotyping of Microsporidia in pet rabbits in China. Results A total of 584 faecal specimens were collected from rabbits in pet shops from four cities in Sichuan province, China. The overall prevalence of microsporidia infection was 24.8% by nested PCR targeting the internal transcribed spacer (ITS) region of E. bieneusi and Encephalitozoon spp. respectively. E. bieneusi was the most common species (n = 90, 15.4%), followed by Encephalitozoon cuniculi (n = 34, 5.8%) and Encephalitozoon intestinalis (n = 16, 2.7%). Mixed infections (E. bieneusi and E. cuniculi) were detected in five another rabbits (0.9%). Statistically significant differences in the prevalence of microsporidia were observed among different cities (χ2 = 38.376, df = 3, P < 0.01) and the rabbits older than 1 year were more likely to harbour microsporidia infections (χ2 = 9.018, df = 2, P < 0.05). Eleven distinct genotypes of E. bieneusi were obtained, including five known (SC02, I, N, J, CHY1) and six novel genotypes (SCR01, SCR02, SCR04 to SCR07). SC02 was the most prevalent genotype in all tested cities (43.3%, 39/90). Phylogenetic analysis showed that these genotypes were clustered into group 1–3 and group 10. Meanwhile, two genotypes (I and II) were identified by sequence analysis of the ITS region of E. cuniculi. Conclusion To the best of our knowledge, this is the first report of microsporidia infection in pet rabbits in China. Genotype SC02 and four novel genotypes were classified into potential zoonotic group 1, suggesting that pet rabbits may cause microsporidiosis in humans through zoonotic transmissions. These findings provide preliminary reference data for monitoring microsporidia infections in pet rabbits and humans.